Seventy-five receipts for pastry, cakes, and sweetmeats - Leslie, Eliza, 1787-1858 (American antiquarian cookbook collection., 2013)
"Eliza Leslie's Seventy-five Receipts for Pastry, Cakes, and Sweetmeats was the first distinctively baking cookbook published in America, as well as the first to share ingredients in a systematic list order at the beginning of each recipe. As Eliza recorded at the time of initial publication, "All the ingredients, with their proper quantities, are enumerated in a list at the head of each receipt, a plan which will greatly facilitate the business of procuring and preparing the requisite article.""--Amazon.com, viewed June 5, 2013.